(untitled) (Proceedings of International Conference on Educational Discoveries and Humanities, 2024)
Cancer has become one of the main problems for health organizations around the world. The risk of developing cancer during a lifetime (up to 75 years of age) is approximately 20%, and the risk of dying from cancer is 10% [1]. One in every five people will be diagnosed with cancer during their lifetime, and one out of ten patients with the disease will die from it. In 2020, 2.26 million new cases of cancer were reported [2]. Breast cancer is the most commonly diagnosed type of cancer in women worldwide and is the leading cause of death among women with the disease[3]. If the current trend in breast cancer continues, it is estimated that by 2040, over 3 million new cases and 1 million deaths will be recorded, solely due to population growth and aging. As of today, various levels of penetrant mutations associated with the risk of developing breast cancer, including mutations in the CHEK2 gene (checkpoint kinase gene), are known [4]. It has been determined that the CHEK2 gene is a susceptibility gene for breast cancer in several populations. In 2002, it was reported that a mutation in the CHEK2 gene could lead to the development of breast cancer, and numerous subsequent studies have confirmed this [5–7].